CD21low B cells reveal a unique glycosylation pattern with hypersialylation and hyperfucosylation - Peter Tobias Felixberger; Peter Tobias Felixberger; Geoffroy Andrieux; Andrea Maul-Pavicic; Andrea Maul-Pavicic; Sigune Goldacker; Sigune Goldacker; Ina Harder; Ina Harder; Sylvia Gutenberger; Sylvia Gutenberger; Jonathan J. M. Landry; et al. (Frontiers in Immunology)
BackgroundThe posttranslational modification of cellular macromolecules by glycosylation is considered to contribute to disease pathogenesis in autoimmune and inflammatory conditions. In a subgroup of patients with common variable immunodeficiency (CVID), the occurrence of such complications is associated with an expansion of naïve-like CD21low B cells during a chronic type 1 immune activation. The glycosylation pattern of B cells in CVID patients has not been addressed to date.ObjectiveThe objective of this study was to examine the surface glycome of B cells in patients with CVID and associated immune dysregulation.MethodsWe performed surface lectin staining on B cells from peripheral blood and tonsils, both ex vivo and after in vitro stimulation. Additionally, we examined the expression of glycosylation-related genes by RNAseq in naïve-like CD21low B cells ex vivo, as well as in naïve CD21pos B cells from healthy controls after in vitro stimulation.ResultsUnlike CD21pos B cells, naïve-like CD21low B cells from CVID patients and CD21low B cells from healthy controls exhibited a unique glycosylation pattern with high levels of α2,6 sialic acids and fucose. This hypersialylation and hyperfucosylation were particularly induced by activation with anti-IgM and interferon-γ (IFN-γ). Transcriptome analysis suggested that naïve-like CD21low B cells possess a comprehensively reorganised glycosylation machinery, with anti-IgM/IFN-γ having the potential to initiate these changes in vitro.ConclusionCD21low B cells are hypersialylated and hyperfucosylated. This may implicate altered lectin-ligand interactions on the cell surface potentially affecting the CD21low B-cell function. These glycome changes appear to be driven by the prominent type I immune response in complicated CVID patients. A better understanding of how altered glycosylation influences immune cell function could lead to new therapeutic strategies.